2008
DOI: 10.1111/j.1439-0523.2007.01476.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cherry incompatibility alleles by microarray

Abstract: We have developed a microarray for identification of sweet cherry incompatibility alleles. Using intron sequence information of the S-RNase gene, we have created a microarray chip that allows the specific recognition of the incompatibility alleles present in a cultivar. Most of the probes designed showed high specificity towards their alleles. In the original set of probes, cross-hybridization was observed between a few alleles with high sequence similarity. As our identification system is based on the combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Finally, this technology has been used in sweet and sour cherry species in the identification of flower incompatibility alleles using other microarray containing only 80 oligonucleotide probes (can be considered a macroarray) corresponding to the first and the second intron of the S-RNase gene (Pasquer et al 2008).…”
Section: Early Transcriptome Analysis Inmentioning
confidence: 99%
“…Finally, this technology has been used in sweet and sour cherry species in the identification of flower incompatibility alleles using other microarray containing only 80 oligonucleotide probes (can be considered a macroarray) corresponding to the first and the second intron of the S-RNase gene (Pasquer et al 2008).…”
Section: Early Transcriptome Analysis Inmentioning
confidence: 99%
“…Microarrays have been extensively used in the past years to study the expression levels of transcripts in many plants including Prunus species [25], [26], [27], [28], [29]. It notably permitted to show in Arabidopsis thaliana that the same set of genes confers resistance or susceptibility to diseases, and that the difference of phenotype is due to the timing and magnitude of the expression of those genes [30].…”
Section: Introductionmentioning
confidence: 99%
“…High-throughput methods have also been developed for S-RNase-based S-genotyping. For instance, microarray platforms based on intron and cDNA sequences have been developed to identify S-RNase alleles in sweet cherry (Pasquer et al, 2008) and Asian pear (Pyrus pyrifolia Nakai) (Nan et al, 2015), respectively. In apple, Larsen et al (2016) identified 25 S-RNase alleles in 432 accessions by using multiplex PCR and fragment detection on a capillary DNA sequencer ( Table 1).…”
Section: Molecular S-genotyping For Successful Crossing and Marker-asmentioning
confidence: 99%